The influence of phase angle on the TMF crack initiation behaviour and damage mechanisms of a single-crystal superalloy - Jonathan Jones (International Journal of Fatigue, 2025)
Thermo-mechanical fatigue (TMF) is a complex damage mechanism considered to be one of the key issues limiting the service lives of hot section components in a gas turbine engine. Turbine blades and nozzle guide vanes are particularly susceptible to this form of material degradation, which results from the simultaneous cycling of mechanical and thermal loads. In this research, a series of TMF tests were undertaken on a single crystal nickel-based superalloy, CMSX-4 under a variety of phase angles and a thermal cycle of 550–1050 °C, to holistically understand the evolving damage mechanisms that can occur under the various loading conditions. The generated data has shown that for the strain ranges tested, fatigue life is significantly affected by the employed phase angle. Furthermore, the length of time that the material is exposed to elevated temperature has a substantial influence on the material’s microstructure, and thus, the dominant mode of damage that occurs.